Perancangan Website Program Studi Sistem Informasi Institut Informatika Dan Bisnis Darmajaya Bandar Lampung - Neni Purwati; Halimah Halimah; Agus Rahardi (Institut Informatika dan Bisnis Darmajaya, 2018)
Informatics Business Institute (IBI) Darmajaya is a private university that prioritizes thr implementation of information technology advancement and business. The information system study program is one of the major in this campus. However, it did not have service facilities that eased the students, alumni and lecturers to gain information abaut the information system. The system development method used in the study was RUP (Rational Unified Process) to be used at the system development with these phases : Inception, Elaboration, Construction and Transition. One the website of the information system study program of IIB Darmajaya Bandar Lampung obtained and proposed would ease the study program of information system to give information to the students, alumni, and lecturers. Tthe data security was wholly managed by administration of information system study program. All information availabel on the website of the study program of information system was inputted into the database, so the problem in inputting faults would be established.Keyword: Website; Study Program of Information System; RUP Method